Longitudinal and Reciprocal Relationships Between Psychological Well-Being and Smoking. Issue 1 (14th September 2018) - Lappan, Sara; Thorne, Christopher B; Long, Dustin; Hendricks, Peter S
Abstract: Introduction: Smoking cessation treatments currently succeed at a rate of approximately 20%–30%, underscoring the importance of exploring factors that might increase intervention effectiveness. Although negative affect has been studied extensively in relation to smoking cessation, psychological well-being (PWB; eg, life satisfaction, optimism, positive affect, purpose in life) has received little attention. This study tested longitudinal and reciprocal relationships between PWB and smoking status in older adults. Methods: Panel data were obtained from the biennial, longitudinal Health and Retirement Study. Using structural equation modeling, we developed cross-lagged models to examine the relationships of PWB in 2006 with smoking status in 2010 and of smoking status in 2006 with PWB in 2010 while controlling for covariates ( N s = 2939–4230, 55% women, 89% white, mean age = 64 years, mean years of education = 13, 25% smokers in 2006 and 21% smokers in 2010). Separate cross-lagged models were developed for each of the PWB variables: life satisfaction, optimism, positive affect, and purpose in life. Results: Greater life satisfaction (standardized path coefficient = −0.04), optimism (standardized path coefficient = −0.07), and positive affect (standardized path coefficient = −0.08) in 2006 predicted a reduced likelihood of smoking in 2010. Being a smoker in 2006 predicted lower life satisfaction (standardized path coefficient = −0.25), optimism (standardized path coefficient = −0.10), positive affect (standardized path coefficient = −0.10), and purpose in life (standardized path coefficient = −0.13) in 2010. Conclusions: Findings warrant further exploration of the relationships between PWB and smoking, and support the incorporation of PWB-boosting components into existing treatments. Implications: Given the relatively low success rate of current smoking cessation treatments, the present results suggest that increasing PWB might promote abstinence and therefore warrant consideration as a focus of future cessation treatment research. Moreover, these results suggest that smoking might inhibit PWB, illuminating a negative consequence of smoking not previously identified. Helping smokers increase their PWB may benefit them beyond promoting cessation and contribute to a flourishing society. These results warrant further investigation of PWB and smoking, and support the continued evaluation of PWB-boosting components in smoking cessation treatments.